1997
DOI: 10.1177/016264349701300302
|View full text |Cite
|
Sign up to set email alerts
|

A Computer-Based System to Prepare Personnel for Family-Centered Interactions in the Individualized Family Service Plan (IFSP) Process

Abstract: This article presents the Verbal Interaction Analysis System (VIAS), a computer-based system designed to analyze verbal interactions, and describes application of the VIAS in analyzing family/professional interactions during the Individualized Family Service Plan (IFSP) process. The VIAS allows for instant data entry, data analysis, data display, and report writing. The VIAS may prove to be a useful observational tool for (a) measuring the quality and quantity of interactions between professionals and families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The Creating a Supportive Environment (CASE) interaction analysis system (previously called VIAS, or Verbal Interaction Analysis System; Johnson et al, 1997) Amidon, 1962). In a given situation, professionals have a choice of using &dquo;direct&dquo; verbal behaviors (e.g., giving information) that minimize the freedom of listeners to respond, or &dquo;indirect&dquo; verbal behaviors (e.g., accepting feelings) that maximize the freedom of listeners to respond (Flanders & Amidon, 1962).…”
Section: Measurementioning
confidence: 99%
See 2 more Smart Citations
“…The Creating a Supportive Environment (CASE) interaction analysis system (previously called VIAS, or Verbal Interaction Analysis System; Johnson et al, 1997) Amidon, 1962). In a given situation, professionals have a choice of using &dquo;direct&dquo; verbal behaviors (e.g., giving information) that minimize the freedom of listeners to respond, or &dquo;indirect&dquo; verbal behaviors (e.g., accepting feelings) that maximize the freedom of listeners to respond (Flanders & Amidon, 1962).…”
Section: Measurementioning
confidence: 99%
“…CASE software performs a number of functions (Johnson et al, 1997), three of which were employed in this study: (a) a reliability file which allows inter-and intraobserver agreement scores to be calculated immediately, (b) summarization of the frequencies and percents of all types and categories of verbal behaviors, and (c) running scripts which identify specific categories of verbal behaviors in sequential order.…”
Section: Measurementioning
confidence: 99%
See 1 more Smart Citation
“…No further statistical report to substantiate this finding or to consider the reliability of the individual categories has been published to date. Additionally, when addressing the validity of the VIAS, Johnson et al (1997) report "the pilot test showed that those videotapes illustrative of family-centered practice and interactions exhibited certain patterns of interaction that were significantly different from the patterns of interactions displayed by those tapes representing nonfamily-centered practice" (p. 23). Again, statistical evidence to support this conclusion has not to date been published.…”
mentioning
confidence: 99%